2016
DOI: 10.1080/15384101.2016.1151585
|View full text |Cite
|
Sign up to set email alerts
|

The homologous recombination component EEPD1 is required for genome stability in response to developmental stress of vertebrate embryogenesis

Abstract: Stressed replication forks can be conservatively repaired and restarted using homologous recombination (HR), initiated by nuclease cleavage of branched structures at stalled forks. We previously reported that the 5′ nuclease EEPD1 is recruited to stressed replication forks, where it plays critical early roles in HR initiation by promoting fork cleavage and end resection. HR repair of stressed replication forks prevents their repair by non-homologous end-joining (NHEJ), which would cause genome instability. Rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Indeed, there is a great deal of evidence that cells will bypass DNA lesions to maintain replication rates [ 41 , 47 ]. We and others have found that even delaying fork repair by 15–30 min can have lethal consequences [ 17 , 19 , 35 , 47 ]. The data presented here suggest a model in which an EEPD1-cleaved replication fork repair intermediate is rapidly recognized by the cell as toxic, and in the absence of BRCA1 and RAD52, the free DS ends are shunted toward the aNHEJ repair pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is a great deal of evidence that cells will bypass DNA lesions to maintain replication rates [ 41 , 47 ]. We and others have found that even delaying fork repair by 15–30 min can have lethal consequences [ 17 , 19 , 35 , 47 ]. The data presented here suggest a model in which an EEPD1-cleaved replication fork repair intermediate is rapidly recognized by the cell as toxic, and in the absence of BRCA1 and RAD52, the free DS ends are shunted toward the aNHEJ repair pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There are two ways to create this DS end: fork reversal to a chicken foot structure, or fork cleavage by a structure-specific nuclease [ 14 16 ]. We previously reported that the 5′ endonuclease EEPD1 could cleave stalled replication forks, initiate EXO1-mediated 5′ end resection, and promote repair of HR replication forks independent of BRCA1 [ 17 19 ]. However, BRCA1/2-mutant cancer cells lack HR, and how these cells repair stalled replication forks has been an unresolved issue.…”
Section: Introductionmentioning
confidence: 99%
“…Next to our study, which is the first to identify EEPD1 as an LXR target and ascribe it a function in cellular sterol homeostasis, 2 other studies from the Hromas group recently reported that EEPD1 has a function in DNA repair in the nucleus. 49 , 50 Wu et al 49 compellingly demonstrated that loss of EEPD1 in several cell types facilitates repair of stressed replication forks induced by DNA-damaging chemicals and that it does so by promoting homologous recombination. In our studies, we have not observed localization of EEPD1 in the nucleus under any of the conditions evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Increased IdU:CldU ratios indicate reduced CldU incorporation after release from stress, i.e. delayed fork restart and/or slower progression ( 69 ). IdU is incorporated prior to HU treatment, so we pooled IdU fiber length measurements from treated and untreated cultures and found that replication speed is not reduced in Metnase or EEPD1 KO cells ( Supplementary Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%